Features of increasing the efficiency of management decisions at “Danisko Ukraine” LLC under the conditions of risk (Economics and region, 2024)
The article examines the essence and significance of management decision-making at a domestic enterprise in the context of risk. The main elements of the overall structure of the management decision-making system were also characterized. The main methods of analysis of efficiency of managerial decision-making at the enterprise are considered, which allow a deeper study of various aspects of the work and conduct of the enterprise in the field of marketing, maintaining financial stability based on various economic indicators of financial statements, formation of logistics distribution channels, development of innovations and implementation of purely new innovative solutions, based on foreign experience, analysis of the features of the production process and the hierarchical structure of interaction between management and employees of the business entity. The main indicators of determining the expert assessment were analyzed: the concordance coefficient, Student's t-test, actual expert assessments, assessment in the case of complete coordination of opinions and the average value of expert assessments. The classification of operational risk of an industrial enterprise is specified. An analysis of the level of consistency of opinions of five experts using the concordance coefficient for the pre-war and post-war period (2019-2023) of “Danisco Ukraine” LLC is provided. The essence of risk management and its main structural features are indicated: a system that unites decision-makers and executors, which establishes links between them and the order of their interaction; activities in the course of which management decisions are made and executed; the purpose of the risk management system is to reduce the impact of unforeseen events on the organization's operations. The main stages of risk management in the context of the enterprise under consideration are characterized. It is highlighted that neural networks are computing systems that are inspired by the structure and functions of the brain. The main types of neural boundaries are defined: Artificial Neural Networks (ANN), Convolutional Neural Networks (CNN), Recurrent Neural Networks (RNNs), Deep Neural Networks (DNNs) and Deep Learning Networks. The software economic maps for enterprises based on a neural network for “Danisco Ukraine” LLC are proposed. It is assumed that this development will help to reduce the negative impact of the risks under consideration on the efficiency of managerial decision-making at industrial enterprises under risk conditions.
Keywords: management decision-making; system; methods of analysis; expert assessment; risk management